The study of the association between the job satisfaction and motivation among the employees at Felda Engineering Services Sdn. Bhd. / Khairatul liza Arshad - Arshad, Khairatul liza (2003)
The movement of workers to act in a desired manner has always consumed the thought of managers. In many ways, this goal has been reached through incentive programs, corporate pep talks, and other types of conditional administrative policy, however, as the workers adjust their behaviour in response to one of the aforementioned stimuli is job satisfaction actualized? The instilling of satisfaction within workers is a crucial task of management satisfaction creates confidence, loyalty and ultimately improved quality in the output of the employed Satisfaction, though, is not the simple result of an incentive program. Employees will most likely not take any more pride in their work even; they win the weekend getaway for having the highest sales. This paper reviews the literature of motivational theorist’s and draws from their approaches to job satisfaction and the role of motivation within job satisfaction. The theories of Frederick Herzberg and Edwin Locke are presented chronologically to show how Locke's theory was a response to Herzberg's theory. By understanding these theories, managers can focus on strategies-of creating job satisfaction